The Influence Of Mother’s Motivation And Preferences On Fish Consumption Behavior In Rural And Urban Families - Ririn Purnama Sari; Istiqlaliyah Muflikhati (Journal of Consumer Sciences, 2018)
The aims of this study is to analyze the differences and the effects of mother’s motivation and preference on behavior of fish consumption in families in rural and urban areas. The research design which used was cross sectional study with purposive location selection in Duwet Village, Pekalongan Regency, and Kandang Panjang, Pekalongan City. The sample in this study is 100 families consisted of 50 families in rural areas and 50 families in urban areas. The results show that urban families prefer fresh sea fish, while rural families prefer pindang fish. The result of multiple linear regression analysis showed that factors affecting the fish consumption behavior of rural family is family size, and per capita income, while fish consumption behavior of urban family  influenced by family size, per capita income, and preference.